Karakteristik Capaian Index Pemberdayaan Gender di Daerah Istimewa Yogyakarta dalam Pembangunan Masyarakat Berbasis Gender 2021 - Muhammad Abi Firmansyah; Soetji Lestari (Syntax Corporation, 2023)
Yogyakarta Special Region Province is the region with the best Gender Empowerment Index (IDG) compared to other provinces in Indonesia. The figures for the Human Development Index (HDI), Gender Development Index (IPG), Gender Empowerment Index (IDG) for the Yogyakarta Special Region Province as a whole are higher than the national scale. The Gender Empowerment Index is an achievement or indicator to measure the implementation of gender justice and equality based on political and economic participation; women need to be empowered so that gender mainstreaming must be the benchmark in every human empowerment program. Gender mainstreaming is a series of strategies for integrating gender perspectives in development and development. Yogyakarta Special Region Province as a province that received the Anugerah Parahita Ekapraya (APE) award three times in 2016, 2018 and 2021; This indicates that the Yogyakarta Special Region Province is good at gender empowerment through gender mainstreaming. Good women's empowerment in each Regency/City region in the Special Region of Yogyakarta Province needs to be reviewed at the characteristics of each region to ensure equitable development and gender empowerment. The regional characteristics of the Special Region of Yogyakarta Province have differences in development and empowerment, Gunung Kidul Regency in this case is still lagging behind in terms of Expected Years of Schooling and Average Years of Schooling, apart from that, Bantul Regency is still lagging behind in terms of women's participation in parliament. Regency/City areas in the Special Region of Yogyakarta Province have different characteristics in the Gender Empowerment Index, equitable development and gender empowerment in the Special Region of Yogyakarta Province are not yet evenly distributed.